バンダ コ ニ オケル エン シュウシ ニ ツイテ - 富山, 千里; トミヤマ, チサト; 北野, 康; キタノ, ヤスシ; Tomiyama, Chisato; Kitano, Yasushi (1984)
P(論文) 南極ライト谷から採取された堆積物コア, DVDP4AとDVDP 14について, 分別溶解法を用いた分析を行った。そして, 堆積物の各構成鉱物への化学元素の分配を明らかにした。それらの結果を用いて, バンダ湖における塩収支を計算し, バンダ湖の年齢を約7000年と見積もることができた。 Two sediment cores, DVDP 4A and DVDP 14 taken from the Wright Valley, Antarctica, were analyzed by using a selective chemical leaching technique. The partitioning of chemical elements into each mineral species in the sediment was clarified. By using the results, the mass balance of salts in Lake Vanda was calculated and the age of Lake Vanda was estimated to be about 7000 years. departmental bulletin paper